Development policies: Sociological perspectives - Anthony Hall (ed.); Midgley, James(ed.) (Manchester, 1988)
Unlike other social scientists, sociologists have not been closely involved in formulating development policies for the Third World nor in their implementation. This volume challenges such a disengaged stance and demonstrates ways in which a sociological perspective can strengthen policy-making. Apart from raising general issues of principle, the book examines sociological involvement in foreign aid, social research, community participation, women in development and models of agrarian policy-making. The book is intended for use at undergraduate and postgraduate level in the disciplines of sociology and development studies, and aims to create interest among economists, planners and public administrators.
Keywords: Economic development-Social aspects